The socio-economic effects of a Marine Protected Area on the ecosystem service of leisure and recreation. (December 2015) - Rees, Siân E.; Mangi, Stephen C.; Hattam, Caroline; Gall, Sarah C.; Rodwell, Lynda D.; Peckett, Frankie J.; Attrill, Martin J.
Abstract: Marine Protected Areas (MPAs) are an important tool for the maintenance of marine ecosystem functionality and health and ensuring the onward flow of beneficial ecosystem services that support human well-being. Social and economic factors influence whether and how stakeholders exploit resources or cooperate to conserve them. Environmental managers are now turning from designating MPAs to monitoring their effectiveness. Combining spatial analysis with quantitative and qualitative survey methods this research shows that an MPA (Lyme Bay, SW England) has had varying effects on the delivery of the beneficial ecosystem service of leisure and recreation. In the survey years 2008–2011 dive businesses have increased their frequency of activity inside and outside the MPA and report an increase in turnover; though they perceive little or no effect of the MPA on business. Charter boat operators have seen an overall decline in the frequency of activity outside the MPA and an increase inside the MPA. They perceive that the MPA has increasingly had a positive effect on their business. Sea angling activity has declined at sites outside the MPA and increased at sites within the MPA, suggesting a redistribution of spatial activity. Diving activity has increased both inside and outside the MPA. Divers report that the MPA has influenced where they choose to dive. This corresponds to a potential increase in value of the MPA resource (represented as the proportional expenditure and associated turnover by these groups) of £2.2 million. This research demonstrates that the use of the resource has changed following designation and that MPAs can attract a greater proportion of the leisure and recreation expenditure and associated turnover to sites within the MPA boundary. Moving forward it is important to assess effects both inside and outside MPAs. Integrating high quality social science at MPA sites to track effectiveness can help to adapt and refine management strategies to reflect the needs of the stakeholders and support effective conservation. Highlights: Spatial analysis and quantitative/qualitative research are used to monitor an MPA. MPAs can attract a greater proportion of leisure and recreation activity. MPAs can attract a greater proportion of expenditure and associated turnover. Social science research can track MPA effects and inform management strategies.